Controlled Generation and Manipulation of Vortex Dipoles in a Bose-Einstein Condensate - Tomohiko Aioi (Physical Review X, 2011)
We propose methods to generate and manipulate vortex dipoles in an atomic Bose-Einstein condensate using Gaussian beams of red- or blue-detuned laser. Vortex dipoles with controlled velocities are shown to be created and launched by a red-detuned beam and by two blue-detuned beams. Critical beam velocities for the vortex nucleation are investigated. The launched vortex dipoles can be trapped, curved, accelerated, and decelerated by using Gaussian laser beams. Collisions between vortex dipoles are demonstrated.